Edukasi Tentang Penyakit Hipertensi kepada Masyarakat Kecamatan Pariangan Kabupaten Tanah Datar - Ifmaily Ifmaily; Ria Afrianti; Rahma Alya; Fakri Alhafizh (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2025)
Hypertension has a fairly high prevalence in Indonesia. The World Health Organization (WHO) in 2015 showed that around 1.13 billion people in the world have hypertension. Basic Health Research (Riskesdas) in 2018 found that the prevalence of hypertension in Indonesia in respondents aged 18 years and above, was found to be 34.8%. The initial survey and based on the results of the Regional Performance Report of Tanah Datar Regency was obtained that 42% of the people of Pariangan District, suffering from hypertension disease, so hypertension education is needed to the people of Pariangan District, Tanah Datar Regency. Education related to the risk factors for hypertension and the management of antihypertensive drugs is a form of education in the form of counseling and the provision of leaflets. Counseling and the provision of leaflets about hypertension are carried out to increase public insight into the risk factors of hypertension and the management of the use of antihypertensive drugs, The purpose of this community service is to provide counseling and provide leaflets to the people of Pariangan District about hypertension disease, both to sufferers and those who do not. This method uses a pre and post test design, where before being given counseling and leaflets, especially for people with hypertension are asked as respondents, then fill out a questionnaire sheet as a pre test, then after being given counseling and leaflets, the community is asked to fill out the questionnaire again as a post test, then data analysis is carried out with a dependent t test. The results of the t dependent test with a p value < 0.05. In conclusion, counseling activities and the provision of leaflets about hypertension to hypertensive patients increase the level of knowledge of hypertension patients related to hypertension.